2018
DOI: 10.1002/chem.201804455
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Electrophilic Cyanation of Boron Enolates: Scope and Mechanistic Studies

Abstract: Chiral β‐ketonitriles bearing a stereogenic carbon center at the α‐position are an important class of compounds, many of which serve as useful synthetic intermediates for the preparation of chiral 1,3‐aminoalcohols, β‐hydroxy nitriles, and related derivatives. Although the enantioselective electrophilic cyanation of enolate equivalents is one of the most promising approaches for the synthesis of chiral β‐ketonitriles, the available methods are largely limited to reactions of 1,3‐dicarbonyl compounds. Herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…General Preparation Method of Arylsulfonyl Cyanide. 20 The compounds were prepared following the reported procedure. H 5 IO 6 (8 equiv) was dissolved in acetonitrile by vigorous stirring for half an hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…General Preparation Method of Arylsulfonyl Cyanide. 20 The compounds were prepared following the reported procedure. H 5 IO 6 (8 equiv) was dissolved in acetonitrile by vigorous stirring for half an hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The spectroscopic studies by Khan et al verified that the N-oxide additive participated in the cyanation of nitroalkenes as a ligand and activator of trimethylsilylcyanide (TMSCN) [23]. Experiments and density functional theory (DFT) calculations by Minakata and co-workers revealed that the cyanation of the boron enolates generated from α,β-unsaturated ketones with ptoluenesulfonyl cyanide (TsCN) proceeded through a six-membered ring transition state (TS) [24]. Based on the NMR spectroscopy results, they proposed that imidazolium cations interacted with the substrate, facilitating the attack of cyanide ions generated by the activation of acetone cyanohydrin by the acetate counter ion in 1-butyl-3-methylimidazolium (BMIM)-based ionic-liquid-catalyzed conjugate cyanation of CF3-substituted alkylidenemalonates [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies by Lu and others successfully demonstrated the power of nucleo-palladation of alkynes and carbon–heteroatom unsaturated bonds insertion cascade in the synthesis of functionalized molecules. Drawing inspiration from this, and in accordance with our interest in developing methods to assemble β-keto­nitriles containing an all-carbon quaternary center, we envisioned a desymmetrizing strategy using conveniently prepared alkyne-tethered malono­nitriles to achieve the synthesis of α-quaternary carbazolones (Scheme D). This proposed transformation involves formation of an arylpalladium­(II) intermediate via trans -amino-palladation of the substrate 1 , followed by a subsequent insertion into the nitrile group , to form carbazolones 2 upon hydrolysis (vide infra, Scheme ).…”
mentioning
confidence: 99%